Islamic banking : the adaptation of banking practice to conform with Islamic law - Homoud, S. H.; Shukri, S. M. (London : Arabian Information, 1985)
This book covers the original basis of the Islamic way of thinking and discusses the most important problems affecting banking activities and commercial activities from the point of view of the Islamic way of tackling the interest (Al-Riba) which is forbidden by the Islamic rules (Al-Sharia)
Includes bibliographical references and footnotes.
ne 18/01/2019
Loans
Keywords: Banks and banking; Islamic countries